2018
DOI: 10.3390/nu10111616
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behaviour Predicts Weight Loss Six Months after Bariatric Surgery: A Longitudinal Study

Abstract: Bariatric surgery is currently the most durable weight loss solution for patients with morbid obesity. The extent of weight loss achieved, however, is subject to variation due to various factors, including patients’ behaviour. In this study, we aimed to identify pre- and post-surgical predictors of weight loss following bariatric surgery. This prospective study included 57 participants who went through bariatric surgery (laparoscopic Roux-en-Y gastric bypass: n = 30; laparoscopic sleeve gastrectomy: n = 23; on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 45 publications
1
32
0
1
Order By: Relevance
“…It is not possible to determine the direction of causality from this data: psychological morbidity could be contributing to suboptimal weight loss and glycaemic improvement or vice versa the suboptimal weight loss and diabetes relapse could be a cause of distress, anxiety and depression. Health related quality of life measures and measures of disordered eating were comparable with other studies of patients after bariatric surgery 29,30 . Eating behaviour appears to become healthier in terms of reduced preference and reward from palatable food after RYGB and VSG surgery 31 .…”
Section: Discussionsupporting
confidence: 71%
“…It is not possible to determine the direction of causality from this data: psychological morbidity could be contributing to suboptimal weight loss and glycaemic improvement or vice versa the suboptimal weight loss and diabetes relapse could be a cause of distress, anxiety and depression. Health related quality of life measures and measures of disordered eating were comparable with other studies of patients after bariatric surgery 29,30 . Eating behaviour appears to become healthier in terms of reduced preference and reward from palatable food after RYGB and VSG surgery 31 .…”
Section: Discussionsupporting
confidence: 71%
“…Bariatric surgery is the leading evidence-based approach in the treatment of obesity, but can it cause or exacerbate eating disorders through the inevitable state of imposed dietary restriction? In this Special Issue, Subramaniam et al [14] reported overall improvement in mental health and eating status six months post-surgery. However, poor mental health and eating prompted by external cues prior to surgery were associated with poorer outcomes post-surgery, highlighting the need to actively address mental health and eating behavior prior to surgery.…”
Section: Treatments Addressing Co-morbidity and Integrated Carementioning
confidence: 99%
“…For example, Kavitha Subramaniam et al, in their prospective study that included 57 patients, the PWL was 23.68% (SD = 7.71). In fact, their study included patients who underwent either LSG or LRYGB, and for the patient who underwent LSG, the PWL was 19.84% (SD = 9.79); a figure notably lesser than the one found in KFSH bariatric centre [12]. We used PWS for reporting weight loss in our study because PWL was found to be the parameter least influenced by preoperative BMI.…”
Section: Postoperative Weight Lossmentioning
confidence: 99%